The Role of Professional Ethics Courses in Producing Prospective Islamic Religious Education Teachers with Character - Iswandi, Iswandi; Syarnubi, Syarnubi; Rahmawati, Ulfah; Lutfiyani, Lutfiyani; Hamrah, Desi (INJIES: Journal of Islamic Education Studies, 2024)
Educator ethics is a moral basis that directs the behavior and actions of educators in carrying out their duties. An educator or prospective educator needs to prioritize main principles such as justice, integrity and character development and apply these values ​​in the learning process. This research aims to identify important characters that must be formed in students so that they can become prospective Islamic Religious Education (PAI) teachers who have good morals and are relevant to the demands of the times. A professional educator does not only depend on material, but also on moral qualities and the application of a professional code of ethics. This research uses a qualitative descriptive method, which describes real situations or phenomena. The research was carried out at STAI YAPTIP West Pasaman in the Islamic Religious Education study program, with a sample of sixth semester students from the class of 2021. The sampling technique used was purposive sampling (based on objectives). Research instruments include questionnaires and interview guidelines. The results of the research show that through optimally designed educational professional ethics lecture activities, students' character values ​​can increase from less active to more active. This research reveals that professional ethics courses play a very important role in forming student character, lecturers contribute with affective assessments to instill character, students need role models from lecturers, and lecturer behavior has a significant impact on student character development. The character of today's students requires further improvement.